Selection of Production Strategies for New Energy Vehicles: An Analysis of the Impact of Government Intervention Policies - Yingxi Ge; Kehong Chen (Systems)
The aim of this study was to analyze the strategic choices and profit variations of a monopolistic automobile manufacturer capable of producing both traditional fuel vehicles and new energy vehicles, with a particular focus on government interventions. Using a theoretical model, the research examined firm-level production decisions by incorporating consumer preferences and market competition under three policy scenarios: no government intervention, government subsidies, and tax policies. The key findings are as follows: (1) In the absence of government intervention, the firm’s production strategy is influenced by consumer preferences for new energy vehicles. Specifically, the firm prioritizes the production of new energy vehicles when consumer preference is high, fuel vehicles when preference is low, and both types when preference is moderate. (2) Government subsidies substantially reduce the production of fuel vehicles while promoting the production of new energy vehicles. However, excessively high subsidies may lead the firm to revert to fuel vehicle production. (3) Tax policies influence production strategies in a manner similar to subsidy policies. (4) When government intervention is weak and competition between fuel vehicles and new energy vehicles is intense, subsidy policies are more effective; however, when competition is less intense, tax policies may be more beneficial. Under strong government intervention, subsidy policies are found to be more effective. This research contributes to the literature by providing a theoretical foundation for government policymaking in the new energy vehicle sector, offering insights into firm-level production decisions under various policy environments. The originality of this study lies in its comparison of the effectiveness of subsidy and tax policies in promoting new energy vehicle production, which helps guide policymakers in designing optimal policy interventions.